Cartera de crédito vencida en la cooperativa de ahorro y crédito san antonio ltda de la parroquia la unión durante el periodo 2022. - Vargas Calvachi, Brayan Ismael (2023)
This work is framed in the analysis of the overdue credit portfolio in the San Antonio LTDA Savings and Credit Cooperative of La Unión Parish during the period 2022, knowing the importance of the credit portfolio for financial institutions. In savings and credit cooperatives, the overdue credit portfolio has become a problem for these financial institutions because these refer to non-payment within the agreed time by the members of the institution. In turn, in this case study, the Financial, Administrative, Tax, Audit and Control Management research line of the Accounting and Auditing career of the Technical University of Babahoyo and the Audit and Control research subline were used, which allowed for a better understanding of the research topic. Furthermore, the methodology implemented was descriptive supported by quantitative and qualitative approaches, which allowed the collection of information in order to obtain a general overview of the research topic and at the same time numerical data was also obtained that allowed us to know the increase in overdue portfolio in the aforementioned period.